Synopsis of Loranthaceae for the São Paulo State, Brazil - Vaz, Leandro Matheus De Carvalho; Souza-Buturi, Fátima Otavina De; Simão-Bianchini, Rosângela (Phytotaxa, 2026)
This paper presents a synopsis of Loranthaceae species occurring in São Paulo State (Brazil), offering essential tools for taxonomic identification. Eighteen species and two varieties of Struthanthus polyrrhizus have been identified within the study area, primarily in the Atlantic Forest. The taxonomic status of S. polyrrhizus var. oblongifolius and S. staphylinus was reestablished. The occurrence of S. polyanthus was confirmed for the study area, exclusively in the Cerrado. We provide three identification keys. For each taxon, we present taxonomic notes, information on general and specific geographical distribution, habitat, iconography, etymology, phenology, a list of analyzed materials, and photographs of the species in the field and laboratory.